Transdisciplinaridade, multiplicidade e devir: uma proposta de experimentação pedagógica para o ensino das literaturas africana e afro-brasileira - Casagrande, Suzana Ceccato (2023)
This thesis is structured around an investigation focused on the training of teachers for the teaching of African and Afro-Brazilian Literature in the Portuguese language. The research seeks to construct pathways that inspire and encourage teachers and future educators to work in a more coherent and engaged manner with African and Afro-Brazilian Literatures in the classroom, considering connections with art in general, culture, history, and the use of technologies available in cyberspace (Lévy, 1993, 1999, 2001). We anchor ourselves in the rhizome theory of Deleuze and Guattari (1988, 1997a, 2010, etc.) as a philosophical foundation and a methodological approach based on the cartographic proposal of Kastrup (2009), Barros (2009), and Passos (2009).The relevance of this approach lies in the need to combat stereotypes, prejudices, and historical gaps and to promote positions for a plural, inclusive, and representative education. The main objective of the research is to propose an innovative pedagogical approach that prompts teachers to work with African and Afro-Brazilian Literature in a critical and reflective manner. It also aims to stimulate the intersection between the literatures addressed and artistic, cultural, and historical expressions, allowing students to understand such connections present in the works. Additionally, the research seeks to highlight the potential of cyberspace technologies as tools to enrich the teaching and learning of these literatures. To achieve this, the research adopts the cartographic proposal as a path, inspired by the idea of mapping and exploring open and constantly changing territories. This approach allows for a flexible and sensitive investigation, where we could follow different paths and connect multiple perspectives. Because cartographic experimentation is used to build a practical and experiential approach, we understand that it motivates teachers to co-create more dynamic and creative pedagogical practices.The rhizomatic philosophical approach rejects hierarchical and linear structures, instead seeking to explore open, horizontal, and multiple connections. By applying rhizomatic knowledge to teacher training, the research emphasizes the importance of valuing non hegemonic knowledge and promoting interaction between different perspectives and knowledge. Exactly for this reason, the perspective of this research consists of a decolonial and resistant gaze. Therefore, our experimentation materialized through the articulation of intervention proposals for classroom practices in Brazilian basic education, especially focused on high school. Our concern was to potentiate encouraging, open, connectable, and usable activities for the teachers and future educators we aim to reach.